2001
DOI: 10.1109/23.983133
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of ionizing radiation-tolerant CMOS APS image sensors up to 30 Mrd (Si) total dose

Abstract: Abstract-An ionizing radiation-tolerant CMOS active pixel sensor (APS) image sensor test chip was designed employing the physical design techniques of enclosed geometry and -channel guard rings. The test chip was fabricated in a standard 0.35-m CMOS process that has a gate-oxide thickness of 7.0 nm. It was irradiated by a -ray source up to a total ionizing radiation dose level of approximately 30 Mrd (Si) and was still functional. The most pronounced effect was the increase of dark current, which was linear wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…The radiation resistance up to the levels of 30 Mrads has been reported [24]. Existing experience may be the guideline for the design of a MAPS device dedicated to EM.…”
Section: Discussionmentioning
confidence: 95%
“…The radiation resistance up to the levels of 30 Mrads has been reported [24]. Existing experience may be the guideline for the design of a MAPS device dedicated to EM.…”
Section: Discussionmentioning
confidence: 95%
“…In order for CMOS APSs to impact upon the medical ionzing applications area, then it needs to demonstrate a significant radiation hardness. Several investigations have been carried out to assess the radiation tolerance of CMOS devices [8], [9] and to propose new design techniques to enhance this performance [10]. In this paper we propose a novel wafer scale CMOS APS, developed in the framework of the Multidimensional Integrated Intelligent Imaging Plus (MI-3 Plus) consortium.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that results presented during this symposium on leakage currents for deeper sub-micron processes indicate that the benefits of this technique may not be significant for processes below 0.13µm feature size. In Figure 5 our measured pixel leakage current values are compared with those reported by Eid et al [8], which have demonstrated survival to 30MRad. In fact this test was halted due to time constraints on the irradiator and not any indication of trouble.…”
Section: Radiation Hardnessmentioning
confidence: 73%